Analisis Pengendalian Kualitas Produk Infusion Stand Menggunakan Metode New Seven Tools dan Failure Mode and Effects Analysis (FMEA) di PT XYZ - Widyawati, Diana; Rochmoeljati, Rr.; Nugraha, Isna (Ekonomis: Journal of Economics and Business, 2025)
This study aims to determine the factors that influence the quality of infusion stand products at PT. XYZ. The research method used in this study is the New Seven Tools method and Failure Mode and Effects Analysis (FMEA). The data collection technique uses interview and observation methods. Based on the results of the study, it is known that the factors that influence defects in infusion stand products are based on human factors, material factors, machine factors, method factors, and environmental factors. It is also known that defects with the highest Risk Priority Number value which will be a priority for repair are broken wheel defects with an RPN value of 280.